KUALITAS MADU LOKAL DARI LIMA WILAYAH DI KABUPATEN BOYOLALI - Nurul Hidayati; Sri Widodo Agung Suedy; Sri Darmanti (Jurnal Pro-Life, 2020)
Honey is a natural sugar produced by bees from flower nectar, extra floral or insect excretion. The quality of honey can be measured with water content, diluted sugar content and acidity. This research aim to determine the quality of local honey from 5 villages in Boyolali Regency. The method used for the measurement of water content and total sugar content is refractometry, while the acidity using titration method. The quantitative data analysis of honey quality were analyzed using Analysis of Variance (ANOVA) and continued with Duncan's Multple Range Test (DMRT) in extent of 95%. The results showed that differences in geographic areas were affected significantly on the quality of honey, with water content ranged between 20.37% - 27.83%, total sugar content of 69.88-77.770Brix, and acidity of 31.86 - 273.95 ml NaOH / Kg. This suggest that the local honey from some areas at Boyolali Regency which is qualified as a good honey based on the goverment’s rules (SNI No. 3454-2013) is honey sample from Kiringan Village. Keywords: honey, Boyolali, quality, local honey